The DeepFaune initiative: a collaborative effort towards the automatic identification of European fauna in camera trap images - Noa Rigoudy; Gaspard Dussert; Abdelbaki Benyoub; Aurélien Besnard; Carole Birck; Jérome Boyer; Yoann Bollet; Yoann Bunz; Gérard Caussimont; Elias Chetouane; Jules Chiffard Carriburu; Pierre Cornette; et al. (European Journal of Wildlife Research, 2023)

Global sensitivities of forest carbon changes to environmental conditions - Simon Besnard; Maurizio Santoro; Oliver Cartus; Naixin Fan; Nora Linscheid; Richard Nair; Ulrich Weber; Sujan Koirala; Nuno Carvalhais (Global Change Biology, 2021)
The responses of forest carbon dynamics to fluctuations in environmental conditions at a global scale remain elusive. Despite the understanding that favourable environmental conditions promote forest growth, these responses have been challenging to observe across different ecosystems and climate gradients. Based on a global annual time series of aboveground biomass (AGB) estimated from radar satellites between 1992 and 2018, we present forest carbon changes and provide insights on their sensitivities to environmental conditions across scales. Our findings indicate differences in forest carbon changes across AGB classes, with regions with carbon stocks of 50–125 MgC ha −1 depict the highest forest carbon gains and losses, while regions with 125–150 MgC ha −1 have the lowest forest carbon gains and losses in absolute terms. Net forest carbon change estimates show that the arc‐of‐deforestation and the Congo Basin were the main hotspots of forest carbon loss, while a substantial part of European forest gained carbon during the last three decades. Furthermore, we observe that changes in forest carbon stocks were systematically positively correlated with changes in forest cover fraction. At the same time, it was not necessarily the case with other environmental variables, such as air temperature and water availability at the bivariate level. We also used a model attribution method to demonstrate that atmospheric conditions were the dominant control of forest carbon changes (56% of the total study area) followed by water‐related (29% of the total study area) and vegetation (15% of the total study area) conditions. Regionally, we find evidence that carbon gains from long‐term forest growth covary with long‐term carbon sinks inferred from atmospheric inversions. Our results describe the contributions from the atmosphere, water‐related and vegetation conditions to forest carbon changes and provide new insights into the underlying mechanisms of the coupling between forest growth and the global carbon cycle.

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Towards a vertebrate demographic data bank - Jean-Dominique Lebreton; Sébastien Devillard; Simon Popy; Marine Desprez; Aurélien Besnard; Jean-Michel Gaillard (Journal of Ornithology, 2012)